Study of The Frequency of Haemoglobinopathies at Premarital Health Screening In Basrah - Meshari, Amna M.; Hameed, Lamis A.; Almousawi, Hayat Y. (Academia Open, 2025)
Background: Hemoglobinopathies are increasingly recognized as a global public health concern, with β-thalassemia major and sickle cell disease posing significant health burdens, particularly in southern Iraq. Specific Background: In response, eight Middle Eastern countries, including Iraq, have implemented mandatory premarital screening and genetic counseling programs to mitigate the transmission of inherited blood disorders. Knowledge Gap: However, limited data exist regarding the prevalence and types of hemoglobinopathies detected through such screening in Basrah province. Aim: This study aimed to determine the frequency of hemoglobinopathies among individuals undergoing premarital screening in Basrah. Results: A retrospective cross-sectional analysis was conducted on 384 randomly selected participants screened between February and June 2018. Females comprised 53.7% and males 46.3% (mean age: 22.8 ± 7.78 years). The prevalence rates were: β-thalassemia trait (2%), sickle cell trait (1.8%), sickle cell anemia (0.2%), sickle-thalassemia (0.5%), Hb D (0.1%), and Hb C (0.2%). A statistically significant association was found between hemoglobinopathies and both consanguinity (33.7%) and positive family history. Novelty: This study provides region-specific epidemiological data on hemoglobinopathies identified through premarital screening. Implications: Findings underscore the need to strengthen genetic counseling and raise awareness about consanguinity-related risks to reduce hereditary blood disorders in the region. Highlight: Beta thalassemia trait was the most common disorder detected. Consanguinity showed significant correlation with hemoglobinopathies. Premarital screening is vital for early genetic risk detection. Keywords: Premarital Screening, Premarital Counselling, Hemoglobinopathy, Thalassemia, Sickle Cell Anemia.